Lending of agroformations: problems and directions of stabilization - Дадашев, Б. А.; Черемісіна, С. Г. (Scientific Progress & Innovations, 2012)
The state and the main problems of the credit mechanism in agriculture of Ukraine is analyzed. Summarized the characteristics and the necessity of collateral activities of agricultural producers in modern economic conditions. The characteristics of the agricultural enterprises that affect their activities with commercial banks. Identified the main causes hindering intensification of credit facilities in the agricultural sector. The basic directions of the stabilization mechanism of agricultural lending units.